Bone Mineral Densitiy of Human Rests with pQCT and DEXA - Suby, Jorge Alejandro (2009)
Bone mineral density (BMD) is a mediating factor of some attritional taphonomic processes. In the last few decades BMD has been successfully employed to assess differential preservation in faunal archaeological samples. In contrast, the BMD of human remains was scarcely studied with taphonomic purposes. Moreover, there is some controversy concerning the reliability of the methods proposed to evaluate this bone property. In this study, we determined the human postcranial volumetric BMD (vBMD) of an archaeological assemblage from Tierra del Fuego (Argentina), with peripheral quantitative computed tomography (pQCT) and area BMD with X-ray densitometry (DEXA). Although the pQCT-assessed vBMD values were more accurate and offer important biomechanical references, the information given by the shape-adjusted vBMD values calculated from DEXA aBMD data is also reliable and provides enough resolution for detection of BMD-related taphonomic processes.